1998
DOI: 10.1111/j.1749-6632.1998.tb09544.x
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Inhibition of Chemokine‐Induced Chemotaxis

Abstract: Chemokines consist of a family of 8-16-kDa cytokines that are generated very early in a wide variety of inflammatory responses and attract leukocytes to local sites. At nanomolar concentrations chemokines initiate signal transduction and activate leukocytes through seven transmembrane receptors (STM), but higher micromolar doses result in homologous desensitizing effects. On the basis of reports that opiates have anti-inflammatory effects and also use STM, we have investigated the possibility that they may cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 28 publications
3
46
1
Order By: Relevance
“…These results demonstrate that the inhibitory effects on IL-8-mediated chemotaxis by the cell-binding fragment of FN was limited to the CXCR1 because the 120-kDa FN fragment had no effect on CXCR2-mediated chemotaxis as tested with the CXCR2-specific chemokine MGSA/GRO␣. Such receptor specificity for desensitization toward IL-8 was recently observed by Grimm et al [23] who demonstrated that met-enkephalin and morphine will inhibit IL-8-mediated chemotaxis but do not affect chemotaxis to the CXCR2-specific chemokine, neutrophil activating peptide-2. Known mechanisms responsible for the desensitization of chemokine receptors involve either down-regulation of the receptor from the cell surface via internalization and/or inhibition of signal transduction pathways as a result of [24] have demonstrated during homologous desensitization of the human CXCR1 receptor by IL-8 that the receptor is susceptible to phosphorylation and has identified specific serine and threonine residues on the cytoplasmic tail of CXCR1 that were required for phosphorylation.…”
Section: Discussionmentioning
confidence: 90%
“…These results demonstrate that the inhibitory effects on IL-8-mediated chemotaxis by the cell-binding fragment of FN was limited to the CXCR1 because the 120-kDa FN fragment had no effect on CXCR2-mediated chemotaxis as tested with the CXCR2-specific chemokine MGSA/GRO␣. Such receptor specificity for desensitization toward IL-8 was recently observed by Grimm et al [23] who demonstrated that met-enkephalin and morphine will inhibit IL-8-mediated chemotaxis but do not affect chemotaxis to the CXCR2-specific chemokine, neutrophil activating peptide-2. Known mechanisms responsible for the desensitization of chemokine receptors involve either down-regulation of the receptor from the cell surface via internalization and/or inhibition of signal transduction pathways as a result of [24] have demonstrated during homologous desensitization of the human CXCR1 receptor by IL-8 that the receptor is susceptible to phosphorylation and has identified specific serine and threonine residues on the cytoplasmic tail of CXCR1 that were required for phosphorylation.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, fMLP was observed to inhibit leukocyte migration induced by the subsequent exposure of the cells to either IL-8 or leukotriene B 4 (22). Opiates, which induce chemotaxis of monocytes, inhibit cell migration induced by chemokines (25). Substance P, which by itself does not induce T cell adhesion to ECM, inhibits RANTES-and MIP-1␤-induced T cell adhesion to FN (26).…”
Section: Discussionmentioning
confidence: 99%
“…Opioids can modulate the immune response by indirect and direct mechanisms (27,28). Indirect modulation occurs when activation of opioid receptors within the CNS modifies the activity of neuroendocrine axes or neurotransmission pathways and then secondarily affects immune functions (27,28). Direct modulation results from the effects of opioids on cells of the immune system, resulting in their dysregulation (22).…”
mentioning
confidence: 99%
“…Morphine can cross the blood brain barrier in sufficient amounts to affect brain function (25,26). Opioids can modulate the immune response by indirect and direct mechanisms (27,28). Indirect modulation occurs when activation of opioid receptors within the CNS modifies the activity of neuroendocrine axes or neurotransmission pathways and then secondarily affects immune functions (27,28).…”
mentioning
confidence: 99%